Earlier surgery improves outcomes from painful chronic pancreatitis. Issue 19 (May 2018) - Ke, Nengwen; Jia, Dan; Huang, Wei; Nunes, Quentin M.; Windsor, John A.; Liu, Xubao; Sutton, Robert
Abstract : Abstract: The timing of surgery for painful chronic pancreatitis (CP) may affect outcomes. Clinical course, Izbicki pain scores, and pancreatic function were retrospectively compared and analyzed between patients undergoing either early or late surgery (< 3 or ≥ 3 years from diagnosis) for painful CP in a single center from 2007 to 2012. The early surgery group (n = 98) more frequently than the late group (n = 199) had abdominal pain with jaundice (22.4% vs 9.5%, P = .002) and pancreatic mass +/− ductal dilatation (47% vs 27%, P < .001), but less frequently abdominal pain alone (73.5% vs 85.9%, P = .009), ductal dilatation alone (31% vs 71%, P < .001), parenchymal calcification (91.8% vs 100%, P < .001) or exocrine insufficiency (60% vs 72%, P = .034); there were no other significant differences. The early group had longer hospital stay (14.4 vs 12.2 days, P = .009), but no difference in complications. Significantly greater pain relief followed early surgery (complete 69% vs 47%, partial 22% vs 37%, none 8% vs 16%, P = .01) with lower rates of exocrine (60% vs 80%, P = .005) and endocrine insufficiency (36% vs 53%, P = .033). Our data indicate that early surgery results in higher rates of pain relief and pancreatic sufficiency than late surgery for chronic pancreatitis patients. Frey and Berne procedures showed better results than other surgical procedures.